2023
DOI: 10.1038/s41598-022-17236-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic acid derivatives for UV-selective and visibly transparent dye-sensitized solar cells

Abstract: Naturally abundant dyes are very attractive for the development of dye-sensitized solar cells (DSSCs). Hydroxycinnamic acid derivatives, such as caffeic acid (CA), ferulic acid (FA), and p-coumaric acid (PA), were considered for the selective harvesting of ultraviolet A (UVA) (315–400 nm) photons. Their spectroscopic and electrochemical properties were investigated both theoretically and experimentally. They were further successfully adopted as photosensitizers in UV-selective and visibly transparent DSSCs, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It was found that the combination of Cu-mordanting with ZnO/polyphenol treatments made the fabrics less reflective, i.e., more absorbent than the unexposed samples in UV-A. The hydroxyl groups from tannin provided good affinity with other molecules, resulting from the formation of hydrogen bonds [53].…”
Section: Effects Of Copper Acetate Mordants On Uv Protection and Chro...mentioning
confidence: 99%
“…It was found that the combination of Cu-mordanting with ZnO/polyphenol treatments made the fabrics less reflective, i.e., more absorbent than the unexposed samples in UV-A. The hydroxyl groups from tannin provided good affinity with other molecules, resulting from the formation of hydrogen bonds [53].…”
Section: Effects Of Copper Acetate Mordants On Uv Protection and Chro...mentioning
confidence: 99%
“…Third generation solar cells, based on perovskites, organic molecular systems or hybrid solutions, such as dye‐sensitized solar cells (DSSCs) need to mature more in terms of long‐term stability, but they are already explored for alternative modes of usage (e. g. integration in tissue) or large scale deployment approaches, like “building‐integrated PV” [1,2] . For the latter in particular, a very appealing prospect is the development of transparent and colorless solar cells, the active materials of which absorb only the invisible near‐UV [3] and near‐IR parts of the sun's spectrum. Since 45 % of sunlight radiation received on Earth lies in the near‐IR (λ≤1700 nm), this part of the spectrum is presently targeted by the development of selectively near‐IR absorbing solar cells (SCs), based either on organic photovoltaics (OPV) [1,4] or on DSSCs [5–7] .…”
Section: Introductionmentioning
confidence: 99%
“…Morin also has UV absorption abilities. The UV absorption wavelength of morin generally ranges from 330 -365 nm (UV A) [7][8].…”
Section: Introductionmentioning
confidence: 99%